Integrated transcriptomic and metabolomic analysis reveal the mechanism of citral production in Camphora officinarum Nees ex Wall leaves - Ling, Qingyan; Zhang, Beihong; Jiang, Junfei; Xiao, Zufei; Zhu, Zhipeng; Huang, Lina; Liu, Yuanqiu; Jin, Zhinong (Frontiers in Plant Science, 2025)
Camphora officinarum Nees ex Wall (C. officinarum), a citral-rich aromatic plant, is recognized as an unrivalled natural source of citral for spice production. Its large-scale cultivation in China via the sustainable coppice-rotation system has markedly revitalized rural economies. Nevertheless, the genetic basis driving its prolific citral accumulation remains elusive. We conducted an integrated transcriptomic and metabolomic analysis comparing three citral type accessions (C1, C2, C3) with a non-citral type control (C0). Metabolomic profiling identified 904 leaf metabolites, with terpenoids representing the most abundant class (19.49%). Strikingly, GC-MS analysis unveiled a monoterpene-dominated essential oil composition in citral type C. officinarum leaves, characterized by four dominant constituents: geranial (36.9%-44.7%), neral (30.7%-34.1%), E-isocitral (2.2%-2.9%), and Z-isocitral (1.5%-2.1%). Integrated transcriptomic and metabolomic analysis highlighted critical key genes, acetyl-CoA C-acetyltransferase (CoAACT), hydroxymethylglutaryl-CoA synthase (CoHMGS), hydroxymethylglutaryl-CoA reductase (CoHMGR), phosphomevalonate decarboxylase (CoMVD), 1-deoxy-D-xylulose-5-phosphate synthase (CoDXS), geranylgeranyl diphosphate synthase, type Ⅲ (CoGGPS), farnesyl diphosphate synthase (CoFDPS) showed elevated expression, enhancing precursor availability. The geraniol synthase (CoGES) and alcohol dehydrogenase (CoADH) involved in citral synthesis were significantly up-regulated in citral type C. officinarum. These findings demonstrate that the quantitative disparities in terpenoid distribution and concentration collectively define the species’ unique aromatic identity, underscoring chemotype-specific metabolic regulation mechanisms, while also screening key genetic determinants of citral biosynthesis preliminarily, thereby laying the groundwork for precision breeding programs in aromatic C. officinarum.